The collision dynamics between double-hump solitons in two mode optical fibers - Weitian Yu; Hongxin Zhang; Abdul-Majid Wazwaz; Wenjun Liu (Results in Physics, 2021)
In this paper, the coupled Manakov equations with variable coefficients, governing the orthogonally polarized pulses transmission in two mode optical fibers, are studied via the Hirota method. The double-hump one- and two-soliton solutions of the Manakov equations are obtained for the first time. Furthermore, the v-type, parabolic, s-type double-hump solitons and the double-hump solitons with phase shift are found. we reveal that the decrease of the distance between two peaks results in the attenuation and amplification. The double-hump solitons have different collision dynamics in different modes. The methods to regulate the phase shift, amplification, collision intensity and splitting of double-hump solitons are investigated. These dynamic analyses will be valuable to increase the capacity of optical fiber communication system and reduce the bit error rate. We also hope that it is helpful for the development of phase shifter, optical amplifier and other optical logic devices.